Exploration of Investigation Regarding Media Ownership in Indonesia in the case of MNC GROUP - Aulia, Fika; Khotimah, Siti; Mahdani, Ajriya; Taqiyuddin, Muhammad Fathi; Nisa, Pia Khoirotun (Raudhah Publisher, 2025)
This study explores the influence of media ownership by MNC Group on press freedom in Indonesia. In the context of democracy, press freedom serves as an important pillar that guarantees the public's right to obtain accurate and objective information. However, the phenomenon of media conglomerates that occurred after the 1998 reform showed that there was a concentration of ownership that could limit the diversity of information and affect the independence of journalists. Through a qualitative approach, this study analyzes how MNC Group, as one of the largest media conglomerates in Indonesia, influences news content and public opinion. The methods used include in-depth interviews, documentation studies, and observations on journalistic practices. The results of the study show that concentrated media ownership has the potential to create bias in reporting, where the media tends to side with the interests of its owners, especially when the owners have political affiliations. The study also identifies the challenges that press freedom faces in the face of media conglomerates and provides recommendations to maintain a balance between press freedom and fair media ownership regulation. This finding is expected to provide insight for policymakers and media practitioners in an effort to strengthen democracy and information disclosure in Indonesia.